Review Article on Swiftlet: Biological Overview, Nest Production, Benefits, and Economic Potential - Mohammad Hasil Tamzil (Jurnal Biologi Tropis, 2026)
Swiftlets, particularly species within the genus Aerodramus, are producers of edible bird’s nests (EBN), a commodity with high economic value in the global market. This article was compiled based on a synthesis of various sources (scientific journals) covering biological, morphological, physiological aspects, nest production mechanisms, as well as the utilization and economic potential of swiftlet nests. Biologically, swiftlets possess morphophysiological adaptations for intensive aerial life, including a form of simple echolocation. The nests are formed from secretions of salivary glands that undergo hypertrophy during the reproductive season and are rich in bioactive glycoproteins. Economically, Indonesia is the world’s leading producer of EBN, contributing significantly to the export market. Conclusion: Swiftlets are EBN-producing birds with very high economic value. Proper management systems and strict control across all aspects of cultivation are required to ensure the sustainability of this genetic resource and its role as a contributor to national foreign exchange.